2014
DOI: 10.1186/1752-1947-8-348
|View full text |Cite
|
Sign up to set email alerts
|

Severe septic shock and cardiac arrest in a patient with Vibrio metschnikovii: a case report

Abstract: IntroductionVibrio metschnikovii is a very rare species and can be fatal to patients with massive comorbidity. Until now only eight other cases have been reported.Case presentationThis case report describes a 78-year-old Danish man who presented with fever, hypotension and unconsciousness and he developed cardiac arrest. Vibrio metschnikovii was identified in all his blood samples and effective antibiotics were initiated.ConclusionsThe human sources are believed to include shrimps, birds, water, sewage and sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…More than a third of these cases also presented with diarrhea, though identified GI symptoms were more frequently associated with nonfatal cases. Additionally, numerous case descriptions have linked foodborne exposure and mild gastroenteritis to progressive disease including necrotic lesions of previously uninjured limbs (31,(47)(48)(49)(50). This review of the literature indicates that disease presentation should not be assumed to indicate the route of exposure; it is likely ingestion of non-cholerae Vibrio spp.…”
Section: Discussionmentioning
confidence: 99%
“…More than a third of these cases also presented with diarrhea, though identified GI symptoms were more frequently associated with nonfatal cases. Additionally, numerous case descriptions have linked foodborne exposure and mild gastroenteritis to progressive disease including necrotic lesions of previously uninjured limbs (31,(47)(48)(49)(50). This review of the literature indicates that disease presentation should not be assumed to indicate the route of exposure; it is likely ingestion of non-cholerae Vibrio spp.…”
Section: Discussionmentioning
confidence: 99%
“…All these cases did not include multidrug‐resistant strains of Vibrio metschnikovii . Another interesting case was septic shock and cardiac arrest in a 78‐year‐old Dutch male caused by Vibrio metschnikovii in 2014 13 . A short review of all clinical cases is shown in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are reports of cases associated with wound infections, mainly in patients exposed to the marine environment, suggesting that V. metschnikovii could have zoonotic potential (Linde et al 2004). A case of severe septic shock and cardiac arrest in a patient with V. metschnikovii was also reported (Jensen and Jellinge 2014). Vibriosis is a disease with worldwide spread in fish, affecting farmed fish under stress conditions (Martínez-Díaz and Anguas-Vélez 2002).…”
Section: Discussionmentioning
confidence: 99%